Guidelines for the management of the social and ethical challenges in brain death during pregnancy. Issue 2 (12th June 2019) - Čartolovni, Anto; Habek, Dubravko
Abstract: The aim of the present study is to assess the ethical, legal, and social issues of brain death in pregnancy through a literature review, and, based on the review results, to provide ethical and social guidelines. A search of PubMed using MeSH terms was conducted and yielded 844 results for the period from 1979 to 2017. After articles were screened based on the title and abstract content, 45 were found to refer to the existing ethical, social, and legal implications in cases of brain death during pregnancy, and 40 articles were selected as the source for our set of ethical and social guidelines. From the findings of the study, issues referring to the legitimacy and justification of performing a corporeal support procedure have been identified, as have the issues focusing on fetus or mother, and, finally, those relating to the decision‐making process. Given the increasing number of successful births after a diagnosis of brain death during pregnancy, there is justification for an ethical duty to continue prolonged corporeal support, even if there is little likelihood of success, despite the apparent absence of a legal duty, and relying on the international jurisdictional discrepancies in the attribution of legal rights to the fetus. Abstract : The increasing number of live infants born to women sustaining prenatal brain death indicates an ethical duty to continue prolonged corporeal support despite lack of legal guidance.